Venture Capital Financing of Innovation Races - Eugen Kovac (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper analyzes innovation races in a moral hazard setting. I develop a model where two competing entrepreneurs, financed by a single venture capitalist, work independently on the same project. The venture capitalist cannot observe the allocation of funds she provides, which creates a moral hazard problem. I identify properties of the optimal financing contract and compare them to two benchmarks: single entrepreneur and first best. In particular, if the entrepreneurs differ in their skills, the relevant question is whether it is profitable to employ the less skilled entrepreneur in addition to the more skilled one. I show that if the entrepreneurs do not differ in their skills too much, financing both of them indeed helps to alleviate the moral hazard problem. Moreover, it might be profitable to finance the less skilled entrepreneur, in addition more skilled one, even in cases where the former would not be employed in the first best.
Keywords: D92; G24; O31; 330